Intussusception in a premature newborn: A case report - Daniel Acosta Farina; Diego León-Ochoa; Karen Serrano-Concha; Manuel Cabrera-Viteri; Jorge Oliveros-Rivero; Daniel Acosta-Bowen (EL-Med-Pub, 2021)
Background: Intussusception is rare in the neonatal period and even less common in premature babies. Case Presentation: We present a case of a premature newborn with an insidious clinical picture characterized by irritability and multiple vomits. Ultrasound was diagnostic of intussusception. The baby had a jejunal intussusception without any pathological lead point, with a favorable outcome. Conclusion: Intussusception is a rare cause of neonatal intestinal obstruction especially in premature neonates.